Do Islamic Financial Resources Affect Profitability Of Islamic Banking? - Falikhatun, Falikhatun; Widaningrum, Rahma; Santoso, Arif Lukman (LPPM ISNJ Bengkalis, 2024)
This study aims to obtain empirical evidence of the influence of Islamic financial resources on the profitability of Islamic banking. Profitability is measured using several ratios, namely return on assets (ROA) and net profit margin (NPM), while the Islamic financial resources used in this study include temporary syirkah fund (TSF), non-performing financing (NPF), asset turnover ratio (ATR), and debt-to-equity ratio (DER). The population of this study is Islamic banking from some member countries of the Organization of Islamic Cooperation (OIC), such as Indonesia, Saudi Arabia, Kuwait, the United Arab Emirates, and Qatar. The research sample used purposive sampling, while the data analysis technique was multiple linear regression. The selected samples were 25 Islamic banks from 2013-2021, and 213 observation data were produced. The results of this study indicate that TSF, NPF, ATR, and DER simultaneously affect the profitability of Islamic banking. However, for partial testing, TSF, NPF, and DER negatively affect profitability, while ATR positively affects profitability. The implications of this study theoretically can be used to add references related to signaling theory in analyzing the phenomenon of fluctuations in Islamic banking profitability. This study has practical implications for Islamic banking management as a reference for utilizing Islamic financial resources following the characteristics of Islamic banking businesses in Indonesia, Saudi Arabia, Kuwait, Qatar, and the United Arab Emirates.